Police referrals for domestic abuse before and during the first COVID-19 lockdown: An analysis of routine data from one specialist service in South Wales. (25th September 2021) - Moore, Graham; Buckley, Kelly; Howarth, Emma; Burn, Anne-Marie; Copeland, Lauren; Evans, Rhiannon; Ware, Lisa
Abstract: Background: COVID-19 lockdown measures may have led to more, and increasingly severe, domestic abuse. This study examines police referrals to a specialist domestic abuse service in Wales, UK before and during the first lockdown. Methods: Routine data relating to 2292 police referrals for female adult victim-survivors from December 2019 until July 2020 were analysed and presented in the form of descriptive statistics to monitor changes in referral rates and the profile of those referrals. Results: There was little increase in the overall volume of police referrals during lockdown, but the proportion assessed as high risk increased, and children became the primary source of third-party referrals, with a higher proportion of reports made by other third parties as restrictions eased. Police reports for cases of Child/Adolescent to Parent Violence (C/APV) occurred almost exclusively during lockdown. Conclusions: The increase in risk level despite less clear increase in volume may suggest unmet need, with victims less likely to seek help during lockdown other than for more severe instances. Increased reports by children suggest increased exposure of children to domestic abuse during school closure. Unmet need for women and children may have been made visible to services, and acquaintances, as measures began to ease.